MODEL PENGEMBANGAN KAPASITAS MANAJEMEN SEKOLAH (SCHOOL CAPACITYBUILDING) UNTUK MENINGKATKAN MUTU PENDIDIKAN - Djam’an Satori; Danny Meirawan; Aan Komariah (Jurnal Administrasi Pendidikan, 2013)
Rendahnya mutu pendidikan yang ditandai dengan rendahnya profesionalisme pendidik dan tenaga kependidikan; kurangnya ketersediaan dan pemanfaatan sarana-prasarana; lemahnya penggalian, manajemen dan akuntabilitas keuangan; dan kurangnya prakarsa/inisiatif berinovasi dalam pengembangan kurikulum merupakan akar masalah perlunya peningkatan kapasitas manajemen sekolah dalam merespons kebutuhan stakeholders dan kemajuan ilmu pengetahuan. Tiga segitiga sama sisi kapasitas yaitu kapasitas individu, kapasitas organisasi, kapasitas kepemimpinan menjadi fokus kajian pengembangan kapasitas manajemen sekolah. Penelitian yang melibatkan mahasiswa ini secara intensif menggunakan metode RD dalam rekabangun model yang paling feasibel untuk membangun kapasitas manajemen sekolah yang efektif dan efisien pada SMA di Jawa Barat. Hasil penelitian menunjukan bahwa pengembangan kapasitas manajemen sekolah dimulai dari peningkatan kemampuan pendidik dan tenaga kependidikan profesional yang dilandasai pengembangan diri secara individual dan kelompok, dilakukan secara kontinu dan dengan penilaian kinerja yang valid. Alat untuk meningkatkan keberlanjutan bagi pengembangan kapasitas manajemen adalah kolegialitas dan prinsip pelaksanaannya adalah berkelanjutan melalui suatu action plan yang terukur. Model yang dikembangkan adalah 4CeeS untuk kepemimpinan bintang 5. 4CS (Casing, Communicating, Competencies, Contribution, Sample), Bintang lima 2 dimensi (Dimensi 1 : spirit-self dicipline, relationship-heart, purpose; Dimensi 2: Constructivistic Leadership-Valuebased leadership-servant leadership; transformationalleadership;visionary leadership)The low quality of education in Indonesia has been indicated by several phenomena, such as the low quality of teachers’ and educational staffs professionalism; the lack of facility, deficiency of educational financing in terms of absorption, budgeting, and accountability; the lack of educational innovations in developing curriculum. Those fundamental problems indicate the need of improvement in terms of capacity development for school management that will be able to response to stakeholder’s needs and scientific development. Importantly, there are three important aspects that should be kept in mind to develop the capacity of school management. Those important aspects are individual, organizational, and leadership capacity. To construct a feasible model that will be able to build an efficient and effective senior high school management in West Java-Indonesia, this study employed a research and development (RD) methodology. The findings revealed that the development of school management was started from the improvements done by teachers and administrators underlined. The improvements made were laid on the foundation of individual and organizational development through managerial tools. One of the tools that could be used was collegiality. It was recommended therefore that the collegiality should be based on measurable action plans that lead to a 4CS model — Casing, Communicating, Competencies, Contribution, and Sample. 4CS model is adopted from five-star leadership that has two dimensions. When the first dimension consists of self-discipline spirit, affective relationship, and purpose, the second dimension consists of constructive, value-based, servant, transformational, and visionary leadership.